2017
DOI: 10.1177/0021934717690526
|View full text |Cite
|
Sign up to set email alerts
|

Feeling No Ways Tired

Abstract: A considerable amount of the literature on African American activism has been focused on the mainstream political participation and the civil rights and Black Power movements. Subsequent research in this era has primarily focused on the church and post-civil war reconstruction efforts. Few contemporary studies have assessed activist efforts among African Americans and the factors that may influence their involvement. The current study investigates what factors are related to activism among African American chu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A third measure, the Multidimensional Measure of Black Activism (Thomas, 2001) is used to assess activism within the African American community as behavior, sociopolitical attitudes, and social change strategies. Multidimensional Measure of Black Activism has been used to examine relationships between racial identity, psychological empowerment, and African American activism (Livingston et al, 2017). Livingston et al found that racial centrality and psychological empowerment were positively related to awareness of anti-Black oppression and ability to mobilize the Black community through activism.…”
Section: Measuring Black Community Activismmentioning
confidence: 99%
“…A third measure, the Multidimensional Measure of Black Activism (Thomas, 2001) is used to assess activism within the African American community as behavior, sociopolitical attitudes, and social change strategies. Multidimensional Measure of Black Activism has been used to examine relationships between racial identity, psychological empowerment, and African American activism (Livingston et al, 2017). Livingston et al found that racial centrality and psychological empowerment were positively related to awareness of anti-Black oppression and ability to mobilize the Black community through activism.…”
Section: Measuring Black Community Activismmentioning
confidence: 99%
“…Additional research on racial identity has indicated that individuals who believe that race is more central to their self-concept are more active within the Black American community and tend to think critically about race and its impact on everyday activities (Neville & Lilly, 2000). Further, in a study by Livingston et al (2017) levels of school pride than Black American HWHS-PW graduates.…”
Section: Discussionmentioning
confidence: 90%
“…Engagement in Black activism is increasing (Livingston et al, 2017), and among young African Americans, activist involvement has been consistently linked to better mental health outcomes (e.g., Chan et al, 2014;LaVeist, 1992;Zimmerman et al, 1999). Considering that the vast majority of Black students are young, emerging adults (Arnett, 2007), it is vital that factors associated with African American activism be identified in order to better understand the mechanisms underpinning this strategy for coping with racial oppression.…”
Section: Resultsmentioning
confidence: 99%